Deciphering solar magnetic activity: The (solar) hale cycle terminator of 2021 - McIntosh, Scott W.; Leamon, Robert J.; Egeland, Ricky (Frontiers in Astronomy and Space Sciences, 2023)
We previously identified an event in the solar timeline that appeared to play a role in how Sunspot Cycle 23 (SC23) transitioned into Sunspot Cycle 24 (SC24). The timeframe for this transition was rapid, taking place over a very short time and perhaps in a time as short as a single solar rotation. Further, we inferred that the transition observed was a critical moment for the Sun's global-scale magnetic field as it was being manifest in the spatially and temporally overlapping magnetic systems belonging to the Sun's 22-year (Hale) magnetic cycle. These events have been dubbed as Hale Cycle terminations, or `terminators' for short. Subsequent exploration of the sunspot record revealed a relationship between terminator separation (as a measure of overlap in the Hale Cycles) and the upcoming sunspot cycle amplitude using a Hilbert transform. Finally, we extrapolated the contemporary sunspots data's Hilbert phase function to project the occurrence of the SC24 terminator in Mid-2020 and inferred that this would result in a large Sunspot Cycle 25 (SC25) amplitude. This paper presents observational evidence that the end of SC24 and the initial growth of SC25 followed a terminator that occurred in mid-December 2021 (approximately 12/13/2021). {\color{blue} Using this December 2021 terminator identification we can finalize our earlier preliminary forecast of SC25 amplitude \-- anticipating a peak total monthly sunspot number of 184$±$17 with 68% confidence, and 184$±$63 with 95% confidence.} Finally, we use other terminator-related superposed epoch analyses developed in parallel work we project the timing of SC25 sunspot maximum to occur between late 2023 to mid 2024.